The Heparan Sulfate Mimetic PG545 Modulates T Cell Responses and Prevents Delayed-Type Hypersensitivity - Koliesnik, Ievgen O.; Kuipers, Hedwich F.; Medina, Carlos O.; Zihsler, Svenja; Liu, Dan; Van Belleghem, Jonas D.; Bollyky, Paul L. (Frontiers in Immunology, 2020)
The heparan sulfate mimetic PG545 (pixatimod) is under evaluation as an inhibitor of angiogenesis and metastasis including in human clinical trials. We have examined the effects of PG545 on lymphocyte phenotypes and function. We report that PG545 treatment suppresses effector T cell activation and polarizes T cells away from Th17 and Th1 and towards Foxp3+ regulatory T cell subsets in vitro and in vivo. Mechanistically, PG545 inhibits Erk1/2 signaling, a pathway known to effect both T cell activation and subset polarization. Interestingly, these effects are also observed in heparanase-deficient T cells, indicating that PG545 has effects that are independent of its role in heparanase inhibition. Consistent with these findings, administration of PG545 in a Th1/Th17-dependent mouse model of a delayed-type hypersensitivity led to reduced footpad inflammation, reduced Th17 memory cells, and an increase in FoxP3+ Treg proliferation. PG545 also promoted Foxp3+ Treg induction by human T cells. Finally, we examined the effects of other heparan sulfate mimetics PI-88 and PG562 on lymphocyte polarization and found that these likewise induced Foxp3+ Treg in vitro but did not reduce Th17 numbers or improve delayed-type hypersensitivity in this model. Together, these data indicate that PG545 is a potent inhibitor of Th1/Th17 effector functions and inducer of FoxP3+ Treg. These findings may inform the adaptation of PG545 for clinical applications including in inflammatory pathologies associated with type IV hypersensitivity responses.